Parameter optimisation for single-track laser cladding using the Taguchi-Grey relational approach - Van Quan Nguyen, Tat Khoa Doan*, Van Nguy Duong, Van Hoang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2026)
The judicious selection of laser cladding (LC) process parameters is essential for the clad bead geometry. In this research, the Taguchi-Grey relational method was chosen to enhance the quality of single-track bead geometry and to perform multi-objective optimisation of process parameters. The Taguchi method was selected to construct an L16 orthogonal experiment. The impact of significant LC parameters (laser power (P), scanning speed (S), and powder feeding rate (F)) on the responses (width (W), height (H), penetration (Pene), and dilution rate) was analysed based on the analysis of variance (ANOVA). The findings indicated that the scanning speed was the most important factor affecting the ratio of layer W, H, Pene, and dilution rate of the cladding. Subsequently, grey relational analysis (GRA) was employed to consolidate the four response variables into a singular grey relational grade (GRG) for quantification and optimisation purposes. Finally, the optimum cladding process parameters were obtained. The face-centred cubic (FCC) single-phase coating was observed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) to analyse the microstructure and chemical composition of the coating. Moreover, hardness measurements exhibited a gradual increase from the substrate (197 HV) to the cladding layer (224 HV), attributed to the distribution of Cr and Mo, solid solution strengthening, and microstructural refinement, demonstrating improved mechanical performance.